(untitled) (The International Journal for Scientific Research, 2023)
Recently, the health of individuals has been considered one of the most important human rights, and medical education has become an economic source and tributary that provides the country with human resources to build a healthy society free of diseases. This research presents a general idea of ​​health medical education and highlights health education activities perspectives that can contribute to the development: the fields of nursing, pharmacy, medical technology, and midwifery. All of them fall within the curricula that respond to the increase by getting acquainted with the paths of medical education in the Al-Batman region. The role of training comes as a difficult task that must be dealt with, highlighted, and focused on the means that work to develop and develop it, and the need to dedicate it in the medical future. It is included within the scientific program of institutes and colleges that supervise medical and health education through the development of teachers and educational leaders. This research proposes to train graduates to become tomorrow’s teachers are not only skilled but also able to keep pace with the ever-evolving world and thinking in deeper areas for the benefit of society, also in the hope that those who can turn to become more involved and active with medical institutions, medical research centers, and health care homes in the future and work to develop advanced medical courses.